A Combined Method Of Data Envelopment Analysis and SERVQUAL Model in Ranking of Service Quality - Alireza Alinezhad (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2018)
In the last decade, despite the extra importance of service and its increasing development in global and national economies, it has received less attention in comparison with manufacturing industries. The evaluation of performance in service organizations has always been one of the main challenges in this area. Parasuraman and colleagues’ five dimensional model is one of the most common models to evaluate the quality of service and was used in this paper to evaluate the service quality in CNG stations in Zanjan Province. In this paper, the Data Envelopment Analysis (DEA) was also used to assess the relative service quality in 36 CNG stations in Zanjan province. Due to the high importance of service quality, it was considered as the functional output of CNG Refueling Stations. The number of employees, number of dispensers, fixed monthly cost, and monthly allocated credit to stations were considered as functional inputs of CNG stations. After obtaining the station’s rank, finally, the sensitivity of results was analyzed using the proposed method of Jahanshahlu and colleagues. Also, the results showed that the developed model of multi criteria data envelopment analysis has better performance than basic models.